Образ оленя у християнському мистецтві України - Забашта, Р. (Студії мистецтвознавчі, 2007)
A Deer – is one of the most widely spread zoomorphic symbol of Christian teaching and its cultural environment, fine arts in particular. It figures in several Bible plots and also in the coresponding icons’ motive. Significance of the deer’s image in Christianity is characterized by rather broad range of concrete idea takings.